2015
DOI: 10.1080/17508487.2016.1117506
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary regimes of ‘care’ and complementary alternative education

Abstract: In schools, the notion of 'care is often synonymous with welfare and disciplinary regimes. Drawing on Foucault, and a study of alternative education across the UK, and looking in depth at two cases of complementary alternative education, we identify three types of disciplinary regimes at work in schools: (1) dominant performative reward and punishment, (2) team building and (3) therapeutic. We argue that while all three regimes aim to steer identified students back to the norm, the two complementary approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The animals are instrumental in supporting this agenda. This can be seen as reproducing dominant enactments of care in mainstream schools that focus on teachers ensuring behavioural compliance (Mills et al, 2017;Thomson & Pennacchia, 2016). However, the above quotes also illustrate the sense that there is more to these animal-child-school relationships that cannot easily be articulated-something which is also noticed by a teacher in Hohti and Tammi's (2019) research with animals and school-age children.…”
Section: Animal-child Relations At Ubuntu Schoolmentioning
confidence: 82%
See 3 more Smart Citations
“…The animals are instrumental in supporting this agenda. This can be seen as reproducing dominant enactments of care in mainstream schools that focus on teachers ensuring behavioural compliance (Mills et al, 2017;Thomson & Pennacchia, 2016). However, the above quotes also illustrate the sense that there is more to these animal-child-school relationships that cannot easily be articulated-something which is also noticed by a teacher in Hohti and Tammi's (2019) research with animals and school-age children.…”
Section: Animal-child Relations At Ubuntu Schoolmentioning
confidence: 82%
“…Furthermore, such caring relations are often seen as "natural" and positive adult-child relations and are seldom interrogated in detail (Ailwood, 2017). Yet, discourses of care are also used to support exclusionary practices in schools, where children with "disruptive" nonconforming behaviours are pushed out of mainstream schooling on the grounds of caring for both them and the other, compliant, children (Graham et al, 2015;Mills et al, 2017;Thomson & Pennacchia, 2016;Tuck, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The research found that these young people experience a lack of support, low trust and disregard from peers and some professionals at a crucial time in their educational careers. Riddell, and Weedon 2015;Malcolm 2015;Thomson and Pennacchia 2016). How young disabled people fare or are marginalised in APs has received limited attention in the literature, further contributing to their marginalisation.…”
Section: Points Of Interestmentioning
confidence: 99%